Working Paper 27: Anti-corruption Collective Action: Success factors, sustainability and strategies (Basel Institute on Governance Working Papers, 2018)
Anti-corruption Collective Action Initiatives (CAIs) are structured efforts that bring together private sector actors with other stakeholders with the aim of preventing corruption and improving the business environment in a particular context.The landscape of CAIs is extremely diverse. Differences cut across the type and number of stakeholders involved. Initiatives can be sector-specific or cross-sectoral. They can be applied at the community, country, regional or global level.This paper is based on two recent workshops in which a wide variety of international Collective Action practitioners shared their experiences, success factors and strategies for overcoming common challenges.For more information about Collective Action, see the B20 Collective Action Hub.
Keywords: Collective Action; Anti-corruption initiative; Multi-stakeholder collaboration